Institusi Wazir, Ceteria dan Menteri pada Abad ke-19: Struktur dan Kuasa Elite dalam Pentadbiran di Kesultanan Melayu Brunei - Haji Mail, Haji Awg Asbol bin (SOSIOHUMANIKA, 2008)
ABSTRACT: This article discusses the formation of the major governing institutions such as Wazir, Ceteria and Manteri of Brunei in 19th century. Such institutions, in fact, manifested the long established governing practices. The appointment of Wazir and Ceteria required strict criteria, including a close relationship to the core nobility or even the Sultanâs kin. However, a Manteri was normally appointed from among the non-nobility (meaning: not Pengiran), who achieved excellence in charisma, leadership and/or influence in society. The Wazir consisted of Pengiran Bendahara, Pengiran Pemanca, Pengiran Digadong, and Pengiran Temenggung. Each of these governing institutions was granted elite roles and power under the paramount leadership of the Sultan. Their power, however, was confined to the status granted to them respectively. Their roles were not limited to political affairs, but also to economy, social development, peopleâs welfare, religion and state customs. The formation of the elite institutions of Wazir, Ceteria and Manteri under the authority of the Sultan had the impact on the social stratification of the ruling class on the one hand, and the ruled on the other, comprising the ordinary members of the population in 19th century. This governing structure had been designed in such a way that succeeded in uplifting the aura of the Brunei Malay Sultanate as well as buttressing the Sultanate family which prevail in the Malay world.Key words: institution of Wazir, Ceteria and Menteri, its positions and roles in the Brunei Malay Suiltanate.Â About the Author: Dr. Haji Awg Asbol bin Haji Mail ialah Pensyarah di Jabatan Sejarah, Fakulti Sastera dan Sains Sosial UBD (Universiti Brunei Darussalam). Beliau dilahirkan di Limbang, Sarawak, pada 24hb Disember 1955. Menamatkan pengajian Sarjana Muda (B.A.Hons.) dari Universiti Brunei Darussalam pada tahun 1989; berkelulusan Sarjana (M.A.) dari universiti yang sama pada tahun 1996; dan berkelulusan program Doktor (Ph.D.) dari Universiti Malaya, Kuala Lumpur, Malaysia, pada tahun 2004, dengan menulis disertasi tentang âKesultanan Brunei Abad ke-19: Sistem Politik dan Struktur Pentadbiranâ. Beliau menulis beberapa buku, diantaranya adalah Sejarah Perkembangan Pendidikan di Brunei, 1950-1985 (Brunei Darussalam: Jabatan Pusat Sejarah Brunei, 2006). Untuk kepentingan akademis, beliau dapat dihubungi dengan alamat e-mail: asbolm@fass.ubd.edu.bnÂ How to cite this article? Haji Mail, Haji Awg Asbol bin. (2008). âInstitusi Wazir, Ceteria dan Menteri pada Abad ke-19: Struktur dan Kuasa Elite dalam Pentadbiran di Kesultanan Melayu Bruneiâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.1 [Mei]. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112, pp.79-114.Chronicle of the article: Accepted (January 28, 2008); Revised (March 26, 2008); and Published (May 20, 2008). Â